Reabilitação de uma arquitectura comum: três casas em Conde, Guimarães - Ana Rita Vale de Araújo (2016)
In Conde, a village in the outskirts of Guimarães, there is an old insistence on building groups of row houses along the edge of the main roads. Regionally, the predominance of factories in the sub-region of the Ave valley led to a spread of this type of housing, during the frst half of the twentieth century, mainly resulting from the need to accommodate the working class. Today, the modesty of these buildings still prevails and the majority of them is still inhabited by the same families - even after the bankruptcy of some of the factories in the region. The present Dissertation of theoretical and practical nature comes from one urge to understand the constructive expression and to fulfll a personal inclination for the subject of popular housing. The three houses that compose the case study stand out as they foster a small community with a different confguration comparing to recent dwellings in the surroundings that consist mostly in two-story villas scattered distantly from each other. The gathered data from the research served directly to inform the design process. In total, there are ten different topics, arranged in no particular order, that support the materialization of the proposed rehabilitation. The development and articulation of the contents were driven by the urge to reinterpret ordinary buildings which initially could not have value. The unifying idea of "Rehabilitation of a common architecture" is the demand to know how one can learn from ordinary architecture, and how it can be adapted to contemporary needs.